Recellularization and Integration of Dense Extracellular Matrix by Percolation of Tissue Microparticles. (23rd June 2021) - Barthold, Jeanne E.; St. Martin, Brittany M.; Sridhar, Shankar Lalitha; Vernerey, Franck; Schneider, Stephanie Ellyse; Wacquez, Alexis; Ferguson, Virginia L.; Calve, Sarah; Neu, Corey P.
Abstract: Cells embedded in the extracellular matrix of tissues play a critical role in maintaining homeostasis while promoting integration and regeneration following damage or disease. Emerging engineered biomaterials utilize decellularized extracellular matrix as a tissue‐specific support structure; however, many dense, structured biomaterials unfortunately demonstrate limited formability, fail to promote cell migration, and result in limited tissue repair. Here, a reinforced composite material of densely packed acellular extracellular matrix microparticles in a hydrogel, termed tissue clay, that can be molded and crosslinked to mimic native tissue architecture is developed. Hyaluronic acid‐based hydrogels are utilized, amorphously packed with acellular cartilage tissue particulated to ≈125–250 microns in diameter and defined a percolation threshold of 0.57 (v/v) beyond which the compressive modulus exceeded 300 kPa. Remarkably, primary chondrocytes recellularize particles within 48 h, a process driven by chemotaxis, exhibit distributed cellularity in large engineered composites, and express genes consistent with native cartilage repair. In addition, broad utility of tissue clays through recellularization and persistence of muscle, skin, and cartilage composites in an in vivo mouse model is demonstrated. The findings suggest optimal material architectures to balance concurrent demands for large‐scale mechanical properties while also supporting recellularization and integration of dense musculoskeletal and connective tissues. Abstract : A new framework for regenerative cartilage scaffolds using acellular extracellular matrix particles, packed beyond a percolation threshold, and crosslinked within chondroinductive hydrogels is presented. The results suggest that the architecture and the packing creates a composite material that balances mechanics, porosity to enable migration, and cellular interactions. Moreover, the technique is applicable to other tissue types.